2000
DOI: 10.1023/a:1011819621859
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We have recently characterized a human bladder cancer cell line T24 and a more aggressive lineage related variant of it, T24T. To gain further insights, we have studied their metastatic ability in an in vivo model system. Results show that T24 forms significantly fewer [4/12 (1/11) mice had metastases with 1-2 lesions/mouse] metastasis in SCID/bg mice than T24T [14/14 (6/6) mice had metastases with a mean of 24-28 lesions/mouse]. To begin exploring the mechanisms underlying this difference, we evaluated the mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Rho GDI-2 is a cytosolic protein participating in the regulation of both the GDP/GTP cycle and the membrane association/dissociation cycle of Rho/ Rac proteins. Rho GDI proteins are in general overexpressed in breast tumors and human bladder cancer and their increased synthesis correlates with malignancy [37,38]. In agreement with our findings, Kovarova et al [39] have reported, by 2-D map analysis followed by MALDI-MS, that Rho GDI proteins are significantly downregulated in CEM T-lymphoblastic leukemia cell lines after treatment with bohemine.…”
Section: Downregulated Proteinssupporting
confidence: 92%
“…Rho GDI-2 is a cytosolic protein participating in the regulation of both the GDP/GTP cycle and the membrane association/dissociation cycle of Rho/ Rac proteins. Rho GDI proteins are in general overexpressed in breast tumors and human bladder cancer and their increased synthesis correlates with malignancy [37,38]. In agreement with our findings, Kovarova et al [39] have reported, by 2-D map analysis followed by MALDI-MS, that Rho GDI proteins are significantly downregulated in CEM T-lymphoblastic leukemia cell lines after treatment with bohemine.…”
Section: Downregulated Proteinssupporting
confidence: 92%
“…It appears, therefore, that rather than constitutive activation, accelerated GDP-GTP exchange may be more important for Rac1-mediated oncogenesis, as is the case for Rac1b. In addition, Seraj et al (2000) have shown that loss of RhoGDI2 expression is associated with invasive and metastatic human cancers. Therefore, the inability of RhoGDI to interact with Rac1b is also consistent with a role for this splice variant in oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PC-SPES was administered orally (gavage) at a concentration of 250 mg/kg/day as previously described (Kubota et al, 2000). Mice were weighed every week and tumor sizes were measured twice a week as described (Seraj et al, 2000). Mice were euthanized 40 days postinjection.…”
Section: In Vivo Tumor Growth and Statistical Analysismentioning
confidence: 99%